PENGARUH PEMULIHAN LAYANAN TERHADAP LOYALITAS PELANGGAN JNE EXPRESS DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi kasus pada mahasiswa FEB UNISMA Prodi Manajemen Angkatan 2017) - Susetyo Puji Choerunnisa; N Rachma; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis reserch aims to determine the effect of service recovery on customer loyalty JNE EXPRESS with customer satisfaction as an intervening variable in FEB UNISMA management class of 2017. The population are who have used JNE EXPRESS services. The sampels were taken using malholtra formula so that obsianed 110 responden qualified as sampels. In this study the data collection techniques used were questionnaires and interviews. The tool used for data analysis in this study is to use a software application in the form of SPSS version 20. The method of analysis in this study uses path analysis. The instrument test in this study was a normality test, reliability test, validity test, t test, Sobel test. The result study shows that service Recovery significantly influences Customer Satisfaction. While Customer Satisfaction has a significant effect on Customer Loyalty and Service Recovery Has a Significant Effect on Customer Loyalty through Customer Satisfaction. Keywords: Service Recovery, Customer Loyalty, Customer Satisfaction